Aru Makassar: Pergeseran Makna dari Sumpah Kesetiaan Prajurit ke Seremonial Sosial Kontemporer - Haslinda Haslinda; Maria Ulviani; Siti Suwadah Rimang (Balai Bahasa Sulawesi Selatan, 2026)
This study aims to analyze the transformation of the meaning of Aru, a traditional symbolic oath in Makassar culture, and to identify the socio-cultural factors influencing its shift from a sacred warrior’s pledge of loyalty to a contemporary ceremonial symbol. The research employs a qualitative descriptive approach with an ethnographic orientation. Data were collected through participant observation, in-depth interviews with traditional leaders, cultural practitioners, and academics, as well as document analysis. The data were analyzed using thematic analysis, involving data familiarization, coding, categorization of themes, interpretation based on cultural symbolic theory, and conclusion drawing. The findings indicate that the meaning of Aru has undergone significant transformation due to modernization, changes in social structure, declining cultural literacy, and the commodification of cultural symbols. Consequently, Aru is increasingly positioned as an aesthetic and ceremonial element rather than a sacred cultural symbol rooted in historical and spiritual values. This study emphasizes the importance of cultural revitalization through education, documentation, and community-based cultural preservation to maintain the symbolic integrity of Aru in contemporary Makassar society. AbstrakPenelitian ini bertujuan untuk menganalisis transformasi makna Aru, yaitu sumpah simbolik dalam budaya Makassar, serta mengidentifikasi faktor-faktor sosial budaya yang memengaruhi pergeserannya dari sumpah kesetiaan sakral prajurit kepada raja menjadi simbol seremonial dalam praktik budaya kontemporer. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan orientasi etnografi. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam dengan tokoh adat, budayawan, dan akademisi, serta studi dokumentasi. Data dianalisis menggunakan analisis tematik melalui tahapan familiarisasi data, proses pengkodean, pengelompokan tema, interpretasi berdasarkan teori simbolik budaya, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pergeseran makna Aru dipengaruhi oleh modernisasi, perubahan struktur sosial, rendahnya literasi budaya, serta komodifikasi simbol budaya. Akibatnya, Aru lebih banyak berfungsi sebagai elemen estetis dan seremonial dibandingkan sebagai simbol sakral yang mengandung nilai historis dan spiritual. Penelitian ini menegaskan pentingnya revitalisasi nilai budaya melalui pendidikan, dokumentasi, dan pelestarian berbasis komunitas untuk menjaga keutuhan makna simbol Aru dalam masyarakat Makassar kontemporer.